Comparative analysis of functional movements screen in elite male and female judo athletes - Kim, T.-W.; Lee, B.; Bae, S.-I. (Research in Dance and Physical Activity, 2024)
The aim of this study was to evaluate the functional movements using the Functional Movement Screen (FMS) in top-ranking male and female judo athletes in Korea, and to compare their ankle and knee range of motion. The study participants included elite male (n=15) and female (n=13) judo athletes. To measure the joint range of motion of the ankle and knee, goniometer measurements were conducted along with the seven movements of the FMS. Data analysis to determine statistical significance among the elite male and female judo athletes was performed using SPSS version 26.0, and the data were processed through an independent samples t-test. The statistical significance level was set at p <0.05. The main findings of this study revealed that in the FMS assessment, the female judo athlete group showed statistically significant higher differences compared to the male athletes in DS, SM, TS. In the TS, 0% (n=13) of female judo athletes scored below 14 points, while 33% (n=15) of male judo athletes did, indicating a gender difference. Moreover, in terms of knee range of motion, the male judo athletes showed statistically significant differences in KFLL and KFLR. In conclusion, the male judo athletes exhibited a higher risk of injury in the FMS assessment compared to the female athletes. Therefore, it is suggested that periodic FMS assessments are necessary to develop a sports science system for injury prevention programs for athletes.